Kepemimpinan Kepala Sekolah, Pengaruhnya terhadap Kompetensi, Motivasi dan Kepuasan Kerja Guru serta Implikasinya pada Kinerja Guru - A Jajang W. Mahri (Kontigensi : Jurnal Ilmiah Manajemen, 2014)
The problem in this study is that the vocational teachers in Indonesia have not been able to demonstrate the adequate work performance. The phenomenon of high and low performance of teachers is predicted by variables that affect it, such as teacher competence, work motivation and job satisfaction, all of which are driven by the variable of principal’s leadership. This study used survey approach with the type of explanation verification research on 366 teachers. Data analysis and interpretation of the results used descriptive analysis and verification (SEM). The result of descriptive analysis indicate that: (a) task-oriented behavior is more prominent in the leadership of principals than relationship-oriented behavior, (b) Not all teachers have a standard of professional competence, (c) Not all teachers demonstrate aspects of the high valence and instrumentality in supporting their performance, (d) There is still a gap between the actual conditions of high employment and expectations about the job in supporting the performance of teachers, mainly due to the dissatisfaction of teachers with the reward system, (e) The performance of teachers has not been fully demonstrated commitment to students and students’ learning, professional knowledge, teaching practice, leadership and school community, and continued professional learning. Results of verification analysis show that the principal’s leadership has a direct impact on teacher competence, work motivation of teachers, and teacher job satisfaction. However, the principal’s leadership does not imply directly to the performance of teachers, but through teacher competence, work motivation of teachers, and teacher job satisfaction. In this way, the principal’s leadership may act more as a driver or enabler that allows an increase in competence, motivation and job satisfaction of teachers so that in turn it would improve teacher the performance.